A Fully-Integrated Memristor Chip for Edge Learning - Zhang, Yanhong; Chu, Liang; Li, Wenjun (Nano-Micro Letters, 2024)
Highlights: 1 The fully-integrated memristor chip for edge learning provides a solid foundation for neural network computation. 2 The fully-integrated memristor chip enables efficient object recognition in noisy backgrounds while minimizing energy consumption. 3 The computing-in-memory chip represents an innovative and interdisciplinary technology that extends beyond multiple research domains.